Mansion [compact disc] - NF (Musician) (Capitol Christian Music Group, 2015)
On NF's debut album, this 23 year-old Gladwin, Michigan native tells his story with lyrical vulnerability complimented by raw energy. His music draws from many real life struggles, including abuse, anger issues, and losing his mother to a drug overdose.